2018
DOI: 10.1159/000495923
|View full text |Cite
|
Sign up to set email alerts
|

Study on Therapeutic Action and Mechanism of TMZ Combined with RITA Against Glioblastoma

Abstract: Background/Aims: Glioblastoma multiforme (GBM) is a malignant and aggressive central nervous system (CNS) tumor with high mortality and low survival rate. Effective treatment of GMB is a challenge worldwide. Temozolomide (TMZ) is a drug used to treat GBM, while the survival period of GBM patients with positive treatment remains less than 15 months. Reactivating p53 and Inducing Tumor Apoptosis (RITA) is a novel potential anti-cancer small molecular drug. Thus, it is essential to discover novel targets or devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Although it is used widely to treat patients with glioma, its effectiveness in treatment is not very high because of TMZ resistant glioma. 48,49 PLK1 is a serine/threonine protein kinase that is an early trigger for G2/M conversion in the cell cycle. 50 Inhibition of PLK1 expression can arrest the cell cycle in the G2/M phase, thereby increasing the effectiveness of chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is used widely to treat patients with glioma, its effectiveness in treatment is not very high because of TMZ resistant glioma. 48,49 PLK1 is a serine/threonine protein kinase that is an early trigger for G2/M conversion in the cell cycle. 50 Inhibition of PLK1 expression can arrest the cell cycle in the G2/M phase, thereby increasing the effectiveness of chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Piperidinones, such as AMG232, are further MDM2-p53 interaction inhibitors, which are tested in a phase I clinical trial in primary and recurrent GBM (NCT03107780) (https://clinicaltrials.gov/ct2/show/NCT03107780, accessed on 30 December 2021). Alternative ways of restoring p53 functions are direct blocking of MDM2 expression via siRNA [82] or restoration of p53 expression via a p53 activator, such as RITA [83]. Similarly, targeting the Rb pathway and CDKs or cyclins drives GBM cells to cell cycle arrest in GBM models [84,85].…”
Section: Targeting the Cell Cycle Machinery In Gbmmentioning
confidence: 99%
“…In vivo in GB, RITA showed synergistic effects when combined with TMZ and an inhibition of cell growth and stemness, as well as apoptosis induction. Interestingly, RITA acted independently of the p53 status ( 156 ). Protein expression studies showed that RITA suppressed cell proliferation by targeting the p53 associated protein ASK1 ( 156 ).…”
Section: Current Status Of Mdm2/x Inhibition and P53 Activation For The Treatment Of Gbmentioning
confidence: 99%
“…Interestingly, RITA acted independently of the p53 status ( 156 ). Protein expression studies showed that RITA suppressed cell proliferation by targeting the p53 associated protein ASK1 ( 156 ). Johansson et al tested its efficacy in combination with the proteasome inhibitor bortezomib and despite showing specific single-agent activity in p53 mut cells, it did not strengthen bortezomib activity ( 154 ).…”
Section: Current Status Of Mdm2/x Inhibition and P53 Activation For The Treatment Of Gbmentioning
confidence: 99%